MANAJEMEN PENDIDIKAN DAN KEPEMIMPINAN KRISTEN DI ERA SOCIETY 5.0 - Novianti Novianti; Selpin Lawa Padang; Oktaria Sambolangi; Kesaktian Panan; Aldianto Borrong Allo (CV. ADIBA AISHA AMIRA, 2023)
In the Era of Society 5.0 marked by technological transformation and rapid social changes, new challenges and opportunities emerge in the fields of education and Christian leadership. The concept of Education Management and Christian Leadership in Era Society 5.0 combines religious principles with technological advancements to shape an education centered on character development, spiritual growth, and service-based leadership. Christian values such as love, justice, and integrity serve as the foundation for making impactful decisions in education and society. Through technological integration, Christian education can offer personalized and adaptive learning experiences that enable students to better develop their potentials. Meanwhile, Christian Leadership in Era Society 5.0 emphasizes leadership based on service, collaboration, and the cultivation of strong character. The use of technology serves as a means to reinforce service and positive impacts within society, while upholding Christian values in decision-making and human relationships. Striking a balance between technology and Christian values becomes pivotal in shaping leaders who guide with love, wisdom, and integrity amidst the challenges of global change and modern complexity.